A new species of Phymaturus from rocky outcrops in the central steppe of Rio Negro province, Patagonia Argentina (Reptilia: Iguania: Liolaemidae) - Scolaro, José Alejandro; Ibargüengoytía, Nora Ruth (Zootaxa, 2007)
A new Phymaturus species called Phymaturus ceii, in the honour of the late Professor José Miguel Cei, is described in the present study. The new species is a member of the “Phymaturus patagonicus” group from Patagonia. It lives at about 1200 m of altitude in a volcanic rocky habitat near to El Cuy plateau, in the central steppe of Rio Negro province, Argentina. The new species and the closely related P. patagonicus are morphologically compared, and its distribution and natural history are pointed out.